Media as a Means of Public Communication: Analysis of the Impact of Social Media on the Formation of Public Opinion - Muhammad Ihsan; Hasrat Efendi Samosir; Khatibah (Jurnal Dakwah dan Komunikasi, 2026)
Purpose − This article aims to deeply analyze the role of social media as a communication tool in building, changing, and even fracturing social relationships in an increasingly digitalized society Method − This research uses a qualitative approach with a desk study method, examining academic literature published in 2023 and later. Findings − Social media has been shown to have a dual role: as a catalyst for the formation of collective solidarity and a space for public advocacy, and as a medium prone to misuse to spread hoaxes, hate speech, and social fragmentation. This study examines how social interactions on digital platforms strengthen public participation in public issues such as social justice, public services, and government policy, but also open up opportunities for horizontal conflict due to widespread disinformation and algorithms that reinforce group bias. Key findings indicate that social media not only accelerates the flow of communication between individuals but also shifts the centers of communication power from formal institutions to informal actors, such as influencers, content creators, and online communities. In the context of public relations, social media serves as a bridge across classes, cultures, and geographic regions, although it often creates digital exclusivity that exacerbates social inequalities.